2010
DOI: 10.1016/j.ijid.2009.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and complications in 1028 cases of brucellosis: a retrospective evaluation and review of the literature

Abstract: In humans, brucellosis may lead to serious morbidity, and it continues to be a major health problem in Turkey. There is no recommended treatment protocol for complicated brucellosis. Large multicenter studies are needed to determine the most appropriate treatment choices and durations in complicated brucellosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

52
540
10
74

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 544 publications
(726 citation statements)
references
References 25 publications
52
540
10
74
Order By: Relevance
“…Since humans are able to report symptoms, human brucellosis typically presents with arthralgia, pyrexia (undulant fever), and fatigue. In a retrospective analysis of 1,028 patients over a 10-year period in Turkey, it was found that gender differences were minimal as to the number of cases (female 52.4% vs. male 47.6%) where the mean age of cases was 33.7 ± 16.34 years [32]. Almost 70% of cases were between the ages of 13–44.…”
Section: Pathogenesis Clinical Presentation and Risk Factor In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…Since humans are able to report symptoms, human brucellosis typically presents with arthralgia, pyrexia (undulant fever), and fatigue. In a retrospective analysis of 1,028 patients over a 10-year period in Turkey, it was found that gender differences were minimal as to the number of cases (female 52.4% vs. male 47.6%) where the mean age of cases was 33.7 ± 16.34 years [32]. Almost 70% of cases were between the ages of 13–44.…”
Section: Pathogenesis Clinical Presentation and Risk Factor In Humansmentioning
confidence: 99%
“…In one study, only five deaths out of 1,028 cases were reported [32]. The major predictor of death was the development of endocarditis.…”
Section: Pathogenesis Clinical Presentation and Risk Factor In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Una respuesta adecuada a terapia anti brucelosis también se aceptó como criterio diagnóstico en aquellos pacientes con cultivos negativos o con serología en títulos no significativos 8 .…”
Section: Materials Y Métodosunclassified
“…Brucellosis may infect almost all of the organs and may cause various complications (1,2). Capillary leak syndrome (CLS) is a rare medical condition where the number and size of pores in the capillaries are increased leading to a leakage of fl uid from the blood to the interstitial fl uid, resulting in dangerously low blood pressure, edema and multiple organ failure due to limited perfusion (3).…”
mentioning
confidence: 99%